Hepatitis E Virus–Associated Meningoencephalitis in a Lung Transplant Recipient Diagnosed by Clinical Metagenomic Sequencing. (13th June 2017) - Murkey, Jamie A.; Chew, Kara W.; Carlson, Margrit; Shannon, Chelsea L.; Sirohi, Deepika; Sample, Hannah A.; Wilson, Michael R.; Vespa, Paul; Humphries, Romney M.; Miller, Steve; Klausner, Jeffrey D.; Chiu, Charles Y.
Abstract: Hepatitis E virus (HEV) infection uncommonly causes chronic hepatitis and neurologic disease. We describe a case of genotype 3a HEV meningoencephalitis diagnosed by metagenomic next-generation sequencing, illustrating the power of an unbiased molecular approach to microbial testing and the first reported case of HEV infection presumably acquired through lung transplantation.